Doing research in design - Crouch, Christopher; Pearce, J. (Berg Publishers, 2012)
Doing Research in Design presents new ways of thinking about the relationship between design and research by positioning design as a social as well as a material practice. This approach emphasises the social consequences of design decisions as well as the importance of the efficient functioning of a design. Doing Research in Design argues that design promotes social change and that, in order to understand that change, designers must turn to social science research methods. The book outlines the relationships between thinking and doing in design - and makes explicit links between design, research, philosophy and sociology - and then examines four central social research methodologies in practice. The aim of Doing Research in Design is to provide anyone involved in the field of design with the knowledge and understanding of the best methods to plan and conduct their research.